Sanción, reposición e indemnización como cons ecuencias autónomas de la infracción administrativa: una lectura a partir del artículo 232.1 de la Ley del Procedimiento Administrativo General - Tírado Barrera, José Antonio (Revista de Derecho, 2019)
The following essay analyzes the relationship between the consequences of an administrativeoffense, in other words, penalty, corrective measure (or remedial) and compensation,as governed by the Administrative Procedure Law General (LPAG-Leydel Procedimiento Administrativo General). With this purpose, Article 232.1 of theLPAG is studied as a general rule governing these relationships and also diverse sectorallegislation is analyzed in order to appreciate the way the legal system has regulatedthese situations in diverse specific situations. It is clear that at policy levelthere is a clear conceptual autonomy between these figures even though it is stillinsufficient to determine all its implications in order to avoid interpretative errorsthat may limit its scope.
Keywords: Administrative offense; administrative sanction; remedial measures; corrective measures; compensation; disciplinary proceedings; complainant